PENGARUH PENGETAHUAN DAN SIKAP TERHADAP KEPATUHAN PENGGUNAAN APD PADA PEKERJA PENGGILINGAN PADI HARUMANSARI KADUNGORA GARUT - Nurrobbi, Zaki Tazkia; Hermana, Dody; Gumilar, Irfan Rizki (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the influence of knowledge and attitudes on compliance with the use of Personal Protective Equipment (PPE) among workers at the Harumansari Rice Mill in Garut. This study was motivated by the low compliance with mask use in a dusty work environment, resulting in many workers experiencing shortness of breath. The study employed a quantitative method with a descriptive approach. The study population consisted of all 32 production workers. The sampling technique used was saturation sampling (census). Data were collected via a Likert-scale questionnaire and analyzed using SEM-PLS. The results indicate that knowledge and attitudes have a positive and significant effect on PPE compliance. An R-Square value of 0.711 indicates that 71.1% of the variation in compliance can be explained by knowledge and attitude. Descriptively, workers’ knowledge falls into the low category (67.75), attitude into the negative category (70.17), and compliance into the low category (68.37). In conclusion, knowledge and attitude are important factors that need to be improved to increase compliance with PPE use. Companies are advised to conduct regular occupational safety training